Diagnosis and treatment of uterine sarcoma: A multicenter, real-world study in western China. Issue 51 (23rd December 2021) - Li, Kemin; Yin, Rutie; Li, Li; Wang, Danqing; Li, Li; Ma, Cailing; Ren, Qianchuan; Wang, Guqing; Fan, Yang; Zhou, Honggui; Liu, Zi; Li, Tao; et al.
Abstract : Abstract: A detailed understanding of the diagnosis and treatment of uterine sarcoma in the real world is required due to its low incidence, high malignancy, lack of specific symptoms, and lack of high-level evidence supporting its clinical diagnosis and treatment. This study aimed to provide a basis for the standardized diagnosis and treatment of uterine sarcoma. It retrospectively analyzed the real-world data on the diagnosis, treatment, and prognosis of uterine sarcoma in western China. The clinical and pathological data of patients with uterine sarcoma diagnosed and treated between January 2009 and January 2019 in 13 medical centers from 4 western provinces of China, Sichuan, Guangxi, Shaanxi, and Xinjiang, were collected and further examined by univariate and multivariate analyses to find possible risk factors affecting the prognosis of uterine sarcoma. A total of 299 patients with various pathological types of uterine sarcoma were included, with an average age of 47.7 ± 11.1 years. The univariate and multivariate analyses showed that age ( P = .0081), family history ( P = .0358), and chemotherapy regimen ( P = .0005) significantly correlated with progression-free survival; while age ( P = .0393) and International Federation of Gynecology and Obstetrics staging ( P = .0141) significantly correlated with overall survival. As age increased, the risk of death in patients with uterine sarcoma increased; The disease tended to progress faster in lower-age patients. A family history of tumors had an impact on disease progression; however, the way in which it affected needs further exploration. Different chemotherapy regimens affected the patient's disease progression. This study suggested that the anthracycline chemotherapy regimen was slightly better.